2022
DOI: 10.3390/biom12020301
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Chemerin and Its Kinetics May Be a Useful Diagnostic and Prognostic Biomarker in Critically Ill Patients with Sepsis: A Prospective Study

Abstract: Chemerin, a novel adipokine, is a potent chemoattractant molecule with antimicrobial properties, implicated in immune responses. Our aim was to investigate circulating chemerin and its kinetics, early in sepsis in critically ill patients and its association with severity and prognosis. Serum chemerin was determined in a cohort of 102 critically ill patients with sepsis during the first 48 h from sepsis onset and one week later, and in 102 age- and gender-matched healthy controls. Patients were followed for 28 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 57 publications
3
22
1
2
Order By: Relevance
“…45, 46 Proinflammatory cytokines are frequently cited as bacteremia biomarkers in the literature. 2, 24, 47-52 In our previous study 1 we showed how this interplay between circulating pro-and anti-inflammatory cytokines impacted the magnitude of the correlated GTPase signals. Thus, GTPase activity in patient leukocytes represents an integrated signaling outcome reflecting the composition of circulating cytokines due to infection.…”
Section: Resultsmentioning
confidence: 94%
“…45, 46 Proinflammatory cytokines are frequently cited as bacteremia biomarkers in the literature. 2, 24, 47-52 In our previous study 1 we showed how this interplay between circulating pro-and anti-inflammatory cytokines impacted the magnitude of the correlated GTPase signals. Thus, GTPase activity in patient leukocytes represents an integrated signaling outcome reflecting the composition of circulating cytokines due to infection.…”
Section: Resultsmentioning
confidence: 94%
“…Circulating chemerin is increased in the early stages of sepsis, especially in patients with septic shock, according to recently published data. Moreover, correlations between chemerin and white blood cells, lactates, CRP and procalcitonin as well as biomarkers of glucose homeostasis were observed [21].…”
Section: Chemerin In Other Diseases In Childrenmentioning
confidence: 97%
“…which it binds [20]. In an animal model, chemerin promoted the adhesion of macrophages to extracellular matrix proteins and adhesion molecules, suggesting its involvement in enhancing the inflammatory response [21]. On the other hand, in the case of acute lung injury, this adipokine affects the reduction of the inflammatory process by reducing neutrophil infiltration and inflammatory cytokine release [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous molecules, such as cytokines and chemokines, involved in the inflammatory cascade in sepsis are being studied to identify better-performing biomarkers [ 7 , 8 ]. In this context, certain adipokines (cytokine-like molecules derived from the adipose tissue) have been recently shown to have diagnostic value in sepsis, while their kinetics early in sepsis were found to be independent predictors of sepsis outcome in prospective observational studies [ 9 , 10 , 11 , 12 , 13 , 14 ]. Moreover, advances in proteomics have supported the investigation of a high number of molecules (the so-called secretome) that are produced and secreted during sepsis [ 15 , 16 ].…”
mentioning
confidence: 99%